Does financial performance really improve the environmental accounting disclosure practices in India: an empirical evidence from nifty companies. (2017) - Omnamasivaya, B.; Prasad, M.S.V.
The study was conducted to examine whether the financial performance really improves environmental accounting disclosure practices of NIFTY companies. For study five years annual reports were taken (2011-2015), environmental accounting disclosure practices was measured by computing an environmental accounting disclosure index and financial performance was measured by using proxies (variables) such as by NPM, ROCE, EPS, DPS, ROA, ROE, P/E, DPR, ROS and MPS. The relationship between average environmental accounting disclosure practices and average financial performance was tested by using multiple regression. The study found positive relationship between average environmental accounting disclosure index and average ROCE, average EPS, average DPS, average ROA, average ROE, average P/E, and average MPS; and on the other hand the study also found negative relationship between average environmental accounting disclosure index and average NPM, average DPR, and average ROS.